2014
DOI: 10.1002/cctc.201301088
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of Submol % Copper‐Catalyzed CN Cross‐Coupling

Abstract: Carbonnitrogen bond formation can be catalyzed by copper in very low concentrations (≈100 ppm), with mechanistic features that are distinct from those in the high‐concentration regime. The reaction was studied by initial rate kinetics, competitive Hammett studies, and DFT calculations. The deprotonation of the model nucleophile, pyrrole, is limited by mass transfer with the heterogeneous base. The positive reaction order in dimethylethylenediamine was explained by this reagent working not only as a ligand to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 105 publications
1
15
0
Order By: Relevance
“…Recently, a similar negative effect of HPO 4 2− was reported by Lu and co‐workers in Ni‐mediated reactions . In this situation, a greater amount of ligand or nucleophile is required to generate the active species ( 3 b / 3 c ) and for mass transfer ( 6 is insoluble in toluene).…”
Section: Resultssupporting
confidence: 65%
“…Recently, a similar negative effect of HPO 4 2− was reported by Lu and co‐workers in Ni‐mediated reactions . In this situation, a greater amount of ligand or nucleophile is required to generate the active species ( 3 b / 3 c ) and for mass transfer ( 6 is insoluble in toluene).…”
Section: Resultssupporting
confidence: 65%
“…In situ formation of the active species. The mechanism of CuI-catalyzed reaction in homogeneous phase has been both experimentally 58 and computationally [59][60][61] studied in the literature. Our study has shown that a two-fold enhancement in activity can be achieved by introducing metal-free GCN material and that nearly quantitative yields can be obtained after 4 h through doping the lattice of GCN with Fe single atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The O‐ or N‐arylation mechanism via the copper‐catalyzed coupling reaction has been studied by the Stahl, Norrby, and Das groups by use of density functional theory (DFT) calculations. The reaction involves transmetallation, binding, deprotonation, oxidation, and reductive elimination steps.…”
Section: Methodsmentioning
confidence: 99%